Inclusão de crianças com deficiências nos primeiros anos do Ensino Fundamental em escola pública: dificuldades apontadas por professores - Marinho, Maria Francisca Braga (2018)
The inclusion of children with disabilities in the public school, both concerning public policies and educational practices cannot take place by chance. Brazil has a great debt with students, target audience of special education. The research problem consists in identifying the challenges which teachers face in the context of inclusion policies of children with disabilities for their schooling process, in the 2nd, 3rd and 4th years of basic education I – 1ST and 2ND cycles. Therefore we adopt, as main objective of the present dissertation, to investigate the challenges faced by teachers in the context of inclusion policies of children with disabilities, in the first years of public school basic education, as well as the following specific objectives: to verify if educational policies correspond to the school inclusion policies’ prerogatives of children with disabilities at the 2nd, 3rd and 4th years of basic education I – 1ST and 2ND cycles; to understand how educational inclusion and children with disabilities’ schooling take place nowadays, and to discuss the paths currently proposed by inclusive school education for children with disabilities in the public school, taking into account the hardships found. The research locus is a Paulista municipal school. The study is based on authors who reinforce the idea that inclusion is meant for all students, regardless of their limitations. Six teachers who work with children with disabilities were interviewed. An overview of the research was outlined making use of studies by Nóvoa (2007), Severino (2016), Szymanski (2014), Canário (1998), Franco (2008), Bardin (2016), Ronca (2015) and other authors who theoretically have guided us. The referential that methodologically conducts this study is presented through semi-structured interviews, content analysis and data categorization. The subjects experienced by teachers in everyday school life of the child with disabilities were dealt with during the discussions. It became clear that the confrontations for educational inclusion of children with disabilities without conditions for quality schooling are still a great problem. According to the interviewed subjects’ answers, we realize that Special Education/Inclusion theme was addressed very little and in a superficial fashion in their formations, not specifically contemplating matters relating to special/inclusive education. The absence of information regarding the proposed subject violates the current norms of respect to diversity. Many students with disabilities are registered in the public system by the parents’ initiative. In order for the school to be able to provide answers to all students, a change of principles, practices, collaborative and supportive structures among all those involved in the process of school inclusion is needed. It requires professional qualification, accessibility, physical structure, pedagogical resources, respect for individual differences, and access to quality public education, equal and for all